1983
DOI: 10.1007/bf01323713
|View full text |Cite
|
Sign up to set email alerts
|

Lack of singlet oxygen formation by photoexcited promazine derivatives in aqueous and ethanolic solutions

Abstract: The EPR detection of nitroxide formation and the observation by thin layer chromatography of the specific 1O2 oxidation product of cholesterol, have been used to appreciate singlet oxygen production by promazine and four of its derivatives during irradiation with near-UV light of ethanolic and aqueous solutions. Within the range of sensitivity of the methods, no 1O2 had been detected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1984
1984
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…We have detected lo2 in ethanol while Decuyper et al (1983) did not. They have estimated the sensitivity of their cholesterol product analysis to be 1.6 pmol of the oxygen-cholesterol adduct per mole of singlet oxygen produced.…”
Section: Discussionmentioning
confidence: 49%
“…We have detected lo2 in ethanol while Decuyper et al (1983) did not. They have estimated the sensitivity of their cholesterol product analysis to be 1.6 pmol of the oxygen-cholesterol adduct per mole of singlet oxygen produced.…”
Section: Discussionmentioning
confidence: 49%
“…Moore(27) has studied a series of phenothiazine tranquilizers in methanol solution and shown that 2,5-dimethylfuran stimulates oxygen uptake in the presence of promethazine, promazine, chlorpromazine, prochlorperazine, trifluperazine and thioridiazine. In contrast, Decuyper and co-workers(28) failed to detect singlet oxygen during the irradiation of ethanol solutions of promazine, triflupromazine, methoxypromazine, and acepromazine using the method of Lion et al (29). Similar results were obtained by the same workers in aqueous solution using cholesterol attached to polystyrene latex beads as the singlet oxygen monitor.…”
mentioning
confidence: 89%